On the Ridging of the South Atlantic Anticyclone Over South Africa: The Impact of Rossby Wave Breaking and of Climate Change - Ivanciu, Ioana; Ndarana, Thando; Matthes, Katja; Wahl, Sebastian; 2 Department of Geography, Geoinformatics and Meteorology University of Pretoria Hartfield South Africa; 1 GEOMAR Helmholtz Centre for Ocean Research Kiel Kiel Germany (Geophysical Research Letters, 2022)
Ridging South Atlantic Anticyclones contribute an important amount of precipitation over South Africa. Here, we use a global coupled climate model and the ERA5 reanalysis to separate for the first time ridging highs (RHs) based on whether they occur together with Rossby wave breaking (RWB) or not. We show that the former type of RHs are associated with more precipitation than the latter type. The mean sea level pressure anomalies caused by the two types of RHs are characterized by distinct patterns, leading to differences in the flow of moisture‐laden air onto land. We additionally find that RWB mediates the effect of climate change on RHs during the twenty‐first century. Consequently, RHs occurring without RWB exhibit little change, while those occurring with RWB contribute more precipitation over the southern and less precipitation over the northeastern South Africa in the future. Plain Language Summary: The high pressure system located above the South Atlantic Ocean occasionally extends eastward over South Africa, leading to winds that blow onshore and carry moisture from the warm waters of the Southwest Indian Ocean to the coast. These events, termed ridging highs (RHs), bring an important contribution to precipitation over the southern and eastern parts of South Africa. Their occurrence is related to the propagation and breaking of atmospheric waves at the boundary between the troposphere and the stratosphere. This study categorizes RHs based on the behavior of atmospheric waves above and shows that events that are accompanied by wave breaking result in more precipitation over South Africa. In addition, model simulations are used to investigate the impact of climate change during the twenty‐first century on RHs and the associated precipitation. Although the model predicts that in total South Africa will experience drier conditions in the future, RHs contribute to this drying trend only in the northeastern part of the country. In the southern part of South Africa, the model simulates that RHs will bring ...